THE IMPACT OF THE IR NUTRIZINC (Oryza sativa) CULTIVATION PROGRAM ON FARMER’S INCOME AND EXCHANGE VALUE IN SERANG REGENCY, BANTEN PROVINCE - Phonika Aryati; Ujang Maman; Akhmad Mahbubi; Lebba (AGRIBUSINESS JOURNAL, 2026)
Stunting has long been a major issue in Indonesia,  the government to implement a policy under the Ministry of Agriculture Regulation No. 39 of 2020, which mandates biofortification of rice varieties, including IR Nutrizinc rice, to improve food quality in Indonesia. This study aims to analyze the impact of the IR Nutrizinc rice cultivation program on farmers’ income and exchange value in Serang Regency, Banten Province, from October 2024 – December 2024. The feasibility analysis showed that IR Nutrizinc rice farming was profitable, as indicated by an R/C ratio greater than 1. The Policy Analysis Matrix (PAM) results showed that the NPCI value of IR Nutrizinc rice was 1.06 (>1), indicating government support through input policies within the IR Nutrizinc program. However, the NPCO value of 0.96 (<1) indicated that the output price received by farmers was still below the ideal economic price. The PCR and DRC values of less than 1 indicated that IR Nutrizinc rice farming was economically efficient and had both competitive and comparative advantages. Nevertheless, the EPC value of 0.95 and PC value of 0.85 showed that policy distortions still caused farmers’ profits to be suboptimal. This condition was also reflected in the SRP value of -0.14, indicating a disincentive effect where private profits were lower than social profits. Despite this, the IR Nutrizinc program still contributed positively to farmer welfare, as reflected by the increase in the farmer exchange rate from 1.03 in non-IR Nutrizinc farming to 1.30 in IR Nutrizinc farming in Serang Regency.